2010
DOI: 10.1111/j.1558-5646.2010.01111.x
|View full text |Cite
|
Sign up to set email alerts
|

Paternal Condition Drives Progeny Sex-Ratio Bias in a Lizard That Lacks Parental Care

Abstract: Sex-allocation theory predicts that females in good condition should preferentially produce offspring of the sex that benefits the most from an increase in maternal investment. However, it is generally assumed that the condition of the sire has little effect on progeny sex ratio, particularly in species that lack parental care. We used a controlled breeding experiment and molecular paternity analyses to examine the effects of both maternal and paternal condition on progeny sex ratio and progeny fitness in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 65 publications
0
36
1
Order By: Relevance
“…Nevertheless, there is growing evidence for the role of paternal effects in adaptive sex allocation (e.g. lizards [53,54]), and further studies in birds are required to rigorously test these possibilities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, there is growing evidence for the role of paternal effects in adaptive sex allocation (e.g. lizards [53,54]), and further studies in birds are required to rigorously test these possibilities.…”
Section: Discussionmentioning
confidence: 99%
“…Since males were also fed the same experimental diet as females (once they were paired to females), one possibility is that paternal condition may influence sex allocation [53]. For example, fathers in inferior condition may reduce provisioning and care to their offspring, potentially providing direct benefits to females for adaptive sex allocation.…”
Section: Discussionmentioning
confidence: 99%
“…In wild populations of brown anoles, I found a similar significant negative relationship between condition and midpiece length. In re-analysis of paternity results from a previous experiment (Cox et al 2011) where males were allowed to copulate ad libitum with a female, I found that males in high condition sired more offspring than males in low condition. In competitive matings between males in the experimental diet treatments where males were limited to a single copulation, there was no effect of condition on fertilization success.…”
Section: Dissertation Specific Aims and Contributionsmentioning
confidence: 99%
“…The brown anole has high rates of multiple paternity , and has extended sperm storage (Chapter 4), making it likely that this species experiences high levels of sperm competition. Additionally, in laboratory breeding designs where two age-matched males were mated to a single female with no male-male competition, large males and males with higher body condition tend to produce more offspring and sons than daughters, suggesting a postcopulatory mechanism that creates these biases (Cox et al 2011; Chapter 4).…”
Section: Dissertation Specific Aims and Contributionsmentioning
confidence: 99%
See 1 more Smart Citation